Engaging Youth: The Role of Social Media in Promoting Public Accountability in Local Government - Elawati, Elawati; Priyambodo, Victoria Kusumaningtyas (E-Jurnal Akuntansi; Vol 35 No 2 (2025), 2025)
This study aims to analyze the influence of youth engagement in social media on public accountability in local government. The research was conducted in the Province of West Nusa Tenggara using the convenience sampling method. Data were collected through the distribution of questionnaires to youth, involving 210 respondents. Data analysis was performed using the Partial Least Square-Structural Equation Model (PLS-SEM) technique. The results of the study indicate that latent engagement, follower engagement, and expressive engagement have a positive influence on public accountability. The implications of these findings highlight the importance of increasing youth awareness and understanding of accountability, as well as encouraging greater collective participation in supporting government transparency.      Keyword: Latent Engagement; Follower Engagement; Expressive Engagement; Public Accountability